2021
DOI: 10.1017/pds.2021.1
|View full text |Cite
|
Sign up to set email alerts
|

3d Sketches in Virtual Reality and Their Effect on Development Times

Abstract: In the product development process, digital support continues to advance. Some work steps during product development are still carried out without assistance. Sketch creation is one of these. Therefore, the content created here is rarely documented due to the effort required for digital transformation. An alternative can be sketching in virtual reality. This article explores whether 3D sketching in VR enables faster sketching and can offer the basic features of hand-drawn sketches. To verify this, a tool for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Researchers have also explored various VR-based tools for creating design solutions. Seybold and Mantwill (2021) examined 3D sketching in VR and observed that the same solution quality can be obtained using VR while achieving faster development times. Nandy et al ( 2023) investigated the design space across immersive and non-immersive interfaces using pre-designed design elements.…”
Section: Vr-based Modelling and Editingmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also explored various VR-based tools for creating design solutions. Seybold and Mantwill (2021) examined 3D sketching in VR and observed that the same solution quality can be obtained using VR while achieving faster development times. Nandy et al ( 2023) investigated the design space across immersive and non-immersive interfaces using pre-designed design elements.…”
Section: Vr-based Modelling and Editingmentioning
confidence: 99%
“…There have been several attempts at comparing non-immersive (2D-sketching, 2D assembly, etc.) and immersive ways (3D Sketching, VR-based assembly) of designing with respect to speed (Seybold and Mantwill, 2021), quality, and creativity (Trump and Shealy, 2023). In this work, four interlinking parameters were used to determine the overall usability of a VR tool with respect to intuitiveness.…”
Section: Key Performance Indicesmentioning
confidence: 99%